Implementasi Pembelajaran Kewirausahaan Untuk Menumbuhkan Sikap Wirausaha Bagi Peserta Didik Program Kesetaraan Paket C Di Sanggar Kegiatan Belajar Surabaya - Sutanto, Wahyuning Budiwati; Rosyanafi, Rofik Jalal (J+PLUS UNESA, 2024)
Education is a process of developing individual skills in the attitudes and behavior of society. The purpose of education is to prepare students through teaching guidance and training for their roles in the future. Therefore, we need educational institutions that are able to realize educational goals. One of them is non-formal education, namely the Learning Activities Pleace Surabaya, which is a non-formal education institution which aims to provide equal package C and vocational education for students. Entrepreneurship learning is one of the education provided by the Surabaya Learning Activity with the aim of providing provisions for students to have the ability or in the field of entrepreneurship through practical entrepreneurship training in a bazaar. The method used is qualitative with participant observation and in-depth interview techniques. The results of this research state that the implementation of entrepreneurship learning to foster an entrepreneurial attitude is that entrepreneurial practice activities are bazaars or stands where students in classes XI and The obstacles to this activity are facilities, capital and the enthusiasm of the students. Researchers also found that instilling an entrepreneurial attitude is giving students the freedom and confidence to be independent in preparing entrepreneurial practice markets, the opportunity and confidence to be creative and innovative in determining product ideas to be created. The opportunity and trust to be responsible for every entrepreneurial practice activity. Then there are supporting and inhibiting factors in achieving successful implementation of entrepreneurship learning.